Ultrathin hafnium oxide ferroelectric film capacitor based on electrode optimization and preparation method thereof
By constructing a six-layer structure ultra-thin hafnium oxide-based ferroelectric film capacitor, the interface engineering of the oxide interlayer and metal layer, combined with rapid annealing treatment, the problems of ferroelectric performance reduction and fatigue effects are solved, and the effects of ferroelectricity improvement and coercive field reduction are achieved.
Patent Information
- Application Number
- CN202411653204.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-07
Smart Images

Figure CN119581225A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of capacitors, and in particular to an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization and a preparation method thereof. Background Art
[0002] With the rapid development of high-tech industries such as the Internet of Things, artificial intelligence, and big data, there is a huge demand for high-performance memory chips. Ferroelectric RAM (FeRAM) based on ferroelectric thin film materials is recognized as one of the most promising new non-volatile memories of the next generation due to its outstanding advantages such as non-volatility, low power consumption, high erase and write cycles, high-speed read and write, high-density storage, and radiation resistance. The existing perovskite ferroelectric materials have serious problems such as size effect and incompatibility with COMS processes, which seriously affect the commercial application of perovskite ferroelectric memory.
[0003] The new hafnium oxide-based ferroelectric film (Fe-HfO2, fluorite structure oxide) has attracted much attention due to its stable nanoscale ferroelectricity and good compatibility with CMOS process. In recent years, the research on the preparation of ferroelectric memory using hafnium oxide-based ferroelectric films has made rapid progress, especially in the application of ferroelectric field effect transistors (FeFET). Due to the advantages of high integration and compatibility with CMOS process of hafnium oxide-based ferroelectric films, the ferroelectric memory prepared by them has rapidly surpassed the ferroelectric memory based on perovskite ferroelectric materials in various performance indicators such as device size, electrical performance and storage capacity. In particular, ultra-thin hafnium oxide-based ferroelectric films have broad application prospects in ferroelectric random access memory (FeRAM) and ferroelectric field effect transistors (FeFET) with higher requirements for low power consumption and high density due to their excellent low power consumption and high density characteristics. However, in the process of reducing the physical size to nanoscale, ultra-thin hafnium oxide-based ferroelectric films have problems such as decreased ferroelectric performance, high coercive field, wake-up effect, and fatigue effect. Summary of the invention
[0004] Based on this, the object of the present invention is to provide a method for preparing an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization.
[0005] A method for preparing an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization comprises the following steps:
[0006] S1 deposits a bottom electrode layer on the substrate;
[0007] S2 grows an oxide intercalation layer on the bottom electrode layer;
[0008] S3 growing a metal layer on the oxide intercalation layer;
[0009] S4 uses a hafnium precursor, a doping element Y precursor, and an oxygen source material to grow a Hf on the metal layer. x Y 1-x O2 ferroelectric thin film layer;
[0010] S5 in Hf x Y 1-x A top electrode layer is grown on the O2 ferroelectric thin film layer to obtain substrate / bottom electrode layer / oxide intercalation layer / metal layer / Hf x Y 1-x Six-layer structure product of O2 ferroelectric thin film layer / top electrode layer;
[0011] S6: performing a rapid annealing treatment on the six-layer structure product in an inert atmosphere to obtain an ultra-thin hafnium oxide ferroelectric film capacitor.
[0012] Compared with the prior art, the invention can effectively suppress the generation of an interface dead layer and excessive oxygen vacancies at the bottom of the HYO ferroelectric thin film by constructing a capacitor with a six-layer structure of substrate / bottom electrode layer / oxide intercalation layer / metal layer / HYO ferroelectric thin film layer / top electrode layer; the six-layer capacitor is rapidly annealed in an inert atmosphere to promote the formation of a ferroelectric orthorhombic phase in the HYO ferroelectric thin film, which not only improves the ferroelectricity but also reduces the coercive field and leakage current, thereby enhancing the fatigue characteristics; meanwhile, the preparation process is simple and controllable, and a large-area high-quality ferroelectric thin film with good uniformity can be prepared, and the prepared ferroelectric thin film has excellent ferroelectric properties and has the potential for commercial production and application.
[0013] Furthermore, the step S2 adopts an atomic layer deposition method, introduces O3 as an oxygen source substance, and grows an oxide intercalation layer with a thickness of 1nm to 5nm on the bottom electrode layer.
[0014] Furthermore, the material of the oxide intercalation layer is any one of tungsten oxide, molybdenum oxide, hafnium oxide, zirconium oxide, and aluminum oxide.
[0015] Furthermore, the step S3 adopts a magnetron sputtering method to grow a metal layer with a thickness of 1 nm to 5 nm on the oxide intercalation layer. The magnetron sputtering conditions are: sputtering power of 20 W to 30 W, sputtering time of 5 s to 60 s, substrate speed of 3 rpm to 10 rpm, heating temperature of 0° C. to 300° C., argon partial pressure of 1.0×10 -1 Pa~5.0×10 -1 Pa.
[0016] Furthermore, the material of the metal layer is any one of tungsten (W), gold (Au), nickel (Ni), platinum (Pt), titanium nitride (TiN), molybdenum (Mo), copper (Cu), and ruthenium (Ru).
[0017] Furthermore, the step S4 adopts an atomic layer deposition method to take a doping element Y precursor and a hafnium precursor, introduce O3 as an oxygen source substance, and grow a Hf with a thickness of 4nm to 10nm on the metal layer. x Y 1-x O2 ferroelectric thin film layer.
[0018] Furthermore, the doping element Y precursor may be a zirconium precursor, a lanthanum precursor, an aluminum precursor, or a silicon precursor.
[0019] Furthermore, the Hf x Y 1-x In the O2 ferroelectric thin film layer, x∈(0.2,0.8).
[0020] Furthermore, the step S5 adopts magnetron sputtering to deposit Hf x Y 1-x A plurality of evenly distributed dot top electrodes are grown on the O2 ferroelectric thin film layer, wherein the diameter of the dot top electrodes is 20um-200um, and the thickness of the dot top electrodes is 30nm-100nm.
[0021] At the same time, the present invention also provides an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization, and the capacitor is made according to any of the above-mentioned methods for preparing an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization.
[0022] Compared with the prior art, the beneficial effects of the ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization of the present invention are the same as the preparation method of the ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization, which will not be described in detail here.
[0023] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a flow chart of the method for preparing the ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization of the present invention;
[0025] Figure 2 A schematic diagram of the structure of a Si / W / WOx / W / HZO / W capacitor prepared in an embodiment of the present invention;
[0026] Figure 3 It is a schematic diagram of the structure of the Si / W / HZO / W capacitor prepared in the comparative example of the present invention;
[0027] Figure 4 Figure 4 (a) is a three-dimensional schematic diagram of a Si / W / WOx / W / HZO / W capacitor prepared in an embodiment of the present invention; Figure 4(b) Cross-sectional image of a representative Si / W / WOx / W / HZO / W capacitor obtained by HRTEM. Figure 4 (c) EDS image corresponding to Figure (b);
[0028] Figure 5 Figure 5 (a) is the GIXRD diffraction spectra of the HZO ultra-thin ferroelectric film in the range of 25° to 33° of the Si / W / WOx / W / HZO / W capacitor in the embodiment of the present invention and the Si / W / HZO / W capacitor in the comparative example; Figure 5 (b) and Figure 5 (c) is the Gaussian peak fitting diagram of the GIXRD diffraction peak; Figure 5 (d) is the relative proportion of o-phase and t / m-phase in the HZO ultra-thin ferroelectric film in the embodiments of the present invention and the comparative examples;
[0029] Figure 6 Figure 6 (a) and Figure 6 (b) is the PV loop of the HZO ultra-thin ferroelectric film of the comparative example and the embodiment; 6(c) is the 2Pr of the HZO film of the comparative example and the embodiment; Figure 6 (d) is the 2Vc of the HZO ultra-thin ferroelectric film of the comparative example and the embodiment; Figure 6 (e) is the PV loop of the HZO ultra-thin ferroelectric film of the comparative example and the embodiment at a scanning voltage of ±2.5V; Figure 6 (f) is the PV loop of the PUND test of the HZO ultra-thin ferroelectric film of the comparative example and the embodiment at a scanning voltage of ±2.5V; Figure 6 (g) is a PV loop comparison diagram of the HZO ultra-thin ferroelectric film of the comparative example tested by randomly selecting 50 independent devices under a ±2V scanning voltage; Figure 6 (h) is a PV loop comparison diagram of the HZO ultra-thin ferroelectric film of the embodiment tested by randomly selecting 50 independent devices under a ±2V scanning voltage; Figure 6 (i) is a comparison chart of the yield of 50 independent devices of the PV loop of the HZO ultra-thin ferroelectric film of the comparative example and the embodiment;
[0030] Figure 7 Figure 7 (a) The pulse is ±1.25V / 10 5 Fatigue characteristics comparison chart at Hz; Figure 7 (b) shows the HZO ultra-thin ferroelectric film of the embodiment at different switching voltages of ±1.25 to 2 V / 10 5 Fatigue characteristics comparison chart at Hz;
[0031] Figure 8A comparison diagram of leakage current-voltage (IV) characteristics of HZO ultra-thin ferroelectric films of comparative example and embodiment;
[0032] Fig. 9 Fig. 9 (a) and Fig. 9 (b) is a PFM test comparison diagram of the HZO ultra-thin ferroelectric film of the comparative example and the embodiment at ±5V writing and ±0.5V reading; Fig. 9 (c) and (d) are the phase loops of the HZO ultra-thin ferroelectric film of the comparative example and the embodiment at ±5V PFM single point test; Fig. 9 (e) and (f) are the phase loop and amplitude response loop of the HZO ultra-thin ferroelectric film of the comparative example and the embodiment under the PFM single point test of ±5V. DETAILED DESCRIPTION
[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the embodiments of the present invention.
[0034] When the physical size of the hafnium oxide-based ferroelectric film is reduced to below 7nm, the capacitor prepared based on the hafnium oxide-based ferroelectric film will have problems such as decreased ferroelectric performance, increased coercive field and leakage current. The prior art prepares HfO2 with high remanent polarization and wide process window by doping zirconium (Zr) elements. 0.5 Zr 0.5 O2 (HZO) ferroelectric film, and by adjusting the proportion of different crystal phases in the HZO film to reduce the coercive field of the HZO film, the HZO ferroelectric film capacitor has excellent fatigue and retention characteristics, while ensuring that the HZO ferroelectric film capacitor has good ferroelectricity. However, when the ferroelectric film used in the capacitor is an integrated HZO ferroelectric film, due to the mutual diffusion of electrode elements and oxygen elements in the HZO ferroelectric film during the growth and annealing of the HZO ferroelectric film, an interface dead layer is formed. The interface dead layer easily induces the formation of the non-ferroelectric phase m-phase of the HZO ferroelectric film and the generation of excessive oxygen vacancies, resulting in a decrease in ferroelectricity and a more likely breakdown of the capacitor.
[0035] To this end, the inventors conducted further experimental research and proposed a method for preparing an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization. In this method, an oxide layer and a metal layer are sequentially grown on the bottom electrode layer, so that the upper and lower interfaces of the metal layer in contact with the HZO ultra-thin ferroelectric film have oxides, and the unidirectional diffusion of oxygen elements between the metal layer and the HZO ferroelectric film is changed into a bidirectional diffusion of oxygen elements between the metal layer and the HZO ferroelectric film and oxygen elements in the oxide layer at the same time, thereby inhibiting the formation of a dead layer and excessive oxygen vacancies at the interface of the HZO ultra-thin ferroelectric film, thereby ensuring that the HZO ultra-thin ferroelectric film has excellent ferroelectricity and fatigue properties.
[0036] For details, please refer to Figure 1, Figure 1 It is a schematic flow chart of a method for preparing an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization proposed in the present invention, which specifically includes the following steps.
[0037] S1: depositing a bottom electrode layer on a substrate.
[0038] The substrate is any one of silicon dioxide / silicon, silicon, germanium, sapphire, mica or gold foil, preferably a lightly doped silicon wafer as the substrate. The substrate should be flattened and chemically cleaned before deposition to ensure that the electrode layer deposition surface is flat and clean. The flatness and cleanliness of the substrate will affect the growth quality of the bottom electrode layer, and thus affect the overall performance of the capacitor.
[0039] The material of the bottom electrode layer is any one of tungsten (W), gold (Au), nickel (Ni), platinum (Pt), titanium nitride (TiN), molybdenum (Mo), copper (Cu), and ruthenium (Ru), preferably tungsten (W). The thickness of the bottom electrode layer is 30nm to 100nm, preferably 40nm.
[0040] The deposition method is a magnetron sputtering method, and the magnetron sputtering conditions are: sputtering power is 20W to 30W, sputtering time is 5min to 30min, substrate speed is 3rpm to 10rpm, heating temperature is 0℃ to 300℃, argon partial pressure is 1.0×10 -1 Pa~5.0×10 -1 Pa. Taking the deposition of a 40 nm tungsten layer as the bottom electrode layer as an example, the magnetron sputtering conditions are set as follows: tungsten (W) target, sputtering power 25 W, sputtering time 8 min, substrate speed 10 rpm, substrate heating temperature 25 ° C, argon partial pressure 3.0 × 10 -1 Pa.
[0041] S2: growing an oxide intercalation layer on the bottom electrode layer.
[0042] The material of the oxide intercalation layer is any one of tungsten oxide, molybdenum oxide, hafnium oxide, zirconium oxide and aluminum oxide, preferably tungsten oxide. The thickness of the oxide intercalation layer is 1 nm to 5 nm, preferably 2 nm.
[0043] Specifically, an atomic layer deposition method is used, O3 is introduced as an oxygen source material, and an oxide intercalation layer is grown on the bottom electrode layer grown in step S1. Taking the growth of tungsten oxide intercalation layer as an example, the conditions of atomic layer deposition are set as follows: the growth temperature is 250°C to 280°C, and the number of cycles of introducing O3 oxygen source material is 10 to 30.
[0044] S3: growing a metal layer on the oxide intercalation layer.
[0045] The material of the metal layer is any one of tungsten (W), gold (Au), nickel (Ni), platinum (Pt), titanium nitride (TiN), molybdenum (Mo), copper (Cu), and ruthenium (Ru), preferably tungsten (W). The thickness of the metal layer is 1nm to 5nm, preferably 2nm.
[0046] The growth method is a magnetron sputtering method, and the magnetron sputtering conditions are: sputtering power is 20W to 30W, sputtering time is 5s to 60s, substrate speed is 3rpm to 10rpm, heating temperature is 0℃ to 300℃, argon partial pressure is 1.0×10 -1 Pa~5.0×10 -1 Taking the growth of a 2nm tungsten metal layer as an example, the magnetron sputtering conditions are set as follows: tungsten (W) target, sputtering power 25W, sputtering time 30s, substrate speed 10rpm, substrate heating temperature 25℃, argon partial pressure 3.0×10 -1 Pa.
[0047] S4: Using hafnium precursor, doping element Y precursor, and oxygen source material to grow a Hf on the metal layer x Y 1-x O2 ferroelectric thin film layer.
[0048] The hafnium precursor is Hf[N(CH3)2]4.
[0049] The doping element Y precursor may be a zirconium precursor Zr[N(CH3)2]4, a lanthanum precursor La(iPrCp)3, an aluminum precursor Al[CH3]3, or a silicon precursor Si[CH3]3.
[0050] The oxygen source substance is O3.
[0051] The Hf x Y 1-x The x in the O2 ferroelectric thin film layer is 0.2 to 0.8. Different element ratios can be obtained by pulse cycle modulation and / or pulse gas flow. Taking the zirconium precursor Zr[N(CH3)2]4 as an example, Hf 0.2 Zr 0.8 O2、Hf 0.3 Zr 0.7 O2、Hf 0.4 Zr 0.6 O2、Hf 0.5 Zr 0.5 O2、Hf 0.6 Zr 0.4 O2、Hf 0.7 Zr 0.3 O2、Hf 0.8 Zr 0.2 Ferroelectric thin film layers with different O2 ratios.
[0052] Specifically, an atomic layer deposition method is used to take a doping element Y precursor and a hafnium precursor, introduce O3 as an oxygen source, and grow a 4nm to 10nm thick Hf on the metal layer. x Y 1-x O2 ferroelectric thin film layer.
[0053] Taking the zirconium precursor Zr[N(CH3)2]4 as an example, the zirconium precursor Zr[N(CH3)2]4 and the hafnium precursor Hf[N(CH3)2] are taken, O3 is introduced as an oxygen source, and Hf with a thickness of 4nm to 10nm is grown on the metal layer grown in step S3. x Zr 1- x O2 (HZO) ferroelectric thin film layer; the conditions for atomic layer deposition are set as follows: the growth temperature is 250℃~280℃, and the number of cycles of introducing O3 oxygen source material is 10~30. 0.5 Zr 0.5 Taking the O2 layer as an example, the growth temperature is set to 280°C, and the number of cycles of introducing O3 oxygen source material is 25.
[0054] S5: In Hf x Y 1-x A top electrode layer is grown on the O2 ferroelectric thin film layer to obtain substrate / bottom electrode layer / oxide intercalation layer / metal layer / Hf x Y 1-x The six-layer structure product of O2 ferroelectric thin film layer / top electrode layer.
[0055] Specifically, the Hf grown in step S4 by magnetron sputtering x Y 1-x A plurality of evenly distributed dot top electrodes are deposited on the O2 ferroelectric thin film layer.
[0056] Wherein, the diameter of the dot top electrode is 20um to 200um, preferably 100um.
[0057] The material of the top electrode is any one of tungsten (W), gold (Au), nickel (Ni), platinum (Pt), titanium nitride (TiN), molybdenum (Mo), copper (Cu), and ruthenium (Ru), preferably tungsten (W).
[0058] The thickness of the top electrode layer is 30 nm to 100 nm, preferably 40 nm.
[0059] The magnetron sputtering conditions of the magnetron sputtering method are as follows: sputtering power is 20W to 30W, sputtering time is 5min to 30min, substrate speed is 3rpm to 10rpm, heating temperature is 0℃ to 300℃, argon partial pressure is 1.0×10 -1 Pa~5.0×10-1 Pa.
[0060] Taking the magnetron sputtering of a tungsten (W) top electrode with a diameter of 100um and a thickness of 40nm as an example, the magnetron sputtering conditions are: sputtering power of 25W, sputtering time of 15min, substrate speed of 10rpm, substrate heating temperature of 25℃, argon partial pressure of 3.0×10 - 1 Pa. The dot top electrode can be directly grown by using a hard mask process or can be etched out by using a photolithography process.
[0061] Hf x Y 1-x The top electrode on the O2 ferroelectric thin film layer stabilizes the Hf by providing the required mechanical stress x Y 1-x The ferroelectric o phase in the O2 ferroelectric thin film layer and the circular top electrode can effectively reduce the metal / Hf x Y 1-x The existence of dead layer and / or oxygen vacancies at the interface between O2 ferroelectric thin film layers reduces leakage current. The use of tungsten dot top electrode not only provides the stress conditions required for the formation of ferroelectric o phase, but also minimizes the loss of device performance caused by the difference in work function of the top and bottom electrode layers.
[0062] S6: Substrate / bottom electrode layer / oxide intercalation layer / metal layer / Hf x Y 1-x The six-layer structure product of O2 ferroelectric thin film layer / top electrode layer is rapidly annealed in an inert atmosphere to obtain an ultra-thin hafnium oxide ferroelectric thin film capacitor (HYO).
[0063] The annealing temperature of the annealing treatment is 400° C. to 600° C., preferably 550° C.; the annealing time is 30s to 60s, preferably 30s; and the heating time is 5s to 30s.
[0064] The inert atmosphere is an inert gas such as N2.
[0065] Through rapid annealing and the clamping stress provided by the bottom electrode layer and the top electrode layer, Hf x Y 1-x The O2 ferroelectric thin film layer obtains a metastable orthorhombic phase, thereby inducing Hf x Y 1-x The ferroelectricity of O2 film. At the same time, during the rapid high-temperature annealing process, the electrode may react with oxygen in the air, resulting in electrode oxidation failure. By introducing inert gas, an inert atmosphere can be formed to effectively prevent the electrode from reacting with oxygen in the air. Annealing temperatures that are too high or too low, as well as annealing times that are too short or too long, may lead to the generation of excess monoclinic phases, which is not conducive to the formation of ferroelectric metastable orthorhombic phases.
[0066] At the same time, the present invention proposes an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization prepared based on the above method, wherein the capacitor comprises a substrate 10, a bottom electrode layer 20, an oxide intercalation layer 30, a metal layer 40, a Hf x Y 1-x O2 ferroelectric thin film layer 50 and top electrode layer 60.
[0067] See also Figure 2 In one embodiment, silicon is used as the substrate, sputtered tungsten is used as the bottom electrode layer, atomic layer deposited tungsten oxide is used as the oxide intercalation layer, sputtered tungsten is used as the metal layer, and atomic layer deposited zirconium and hafnium are used as Hf x Zr 1-x O2 ferroelectric thin film layer, sputtered tungsten as the top electrode, to obtain silicon substrate / tungsten bottom electrode layer / tungsten oxide intercalation layer / metal tungsten layer / Hf x Zr 1-x An ultra-thin hafnium oxide ferroelectric film capacitor with a six-layer structure of O2 ferroelectric film layer / tungsten top electrode layer (Si / W / WOx / W / HZO / W).
[0068] See also Figure 3 , which is a comparative example with the above embodiment, with silicon as the substrate, sputtered tungsten as the bottom electrode layer, atomic layer deposition of zirconium and hafnium as Hf x Zr 1-x O2 ferroelectric thin film layer, sputtered tungsten as the top electrode, and silicon substrate / tungsten bottom electrode layer / Hf x Zr 1-x The ultra-thin hafnium oxide ferroelectric film capacitor has a four-layer structure of O2 ferroelectric film layer / tungsten top electrode layer (Si / W / HZO / W). x Zr 1-x The preparation process and thickness of the O2 ferroelectric thin film layer and the tungsten top electrode layer are the same as those in the above embodiment.
[0069] Performance analysis of embodiments and comparative examples
[0070] The following is a performance analysis of the ultra-thin hafnium oxide ferroelectric film capacitors of the embodiments and comparative examples.
[0071] (I) Structural analysis of Si / W / WOx / W / HZO / W capacitors
[0072] 1. Test instrument:
[0073] High Resolution Transmission Electron Microscopy (HRTEM)
[0074] Energy Dispersive Spectroscopy (EDS)
[0075] 2. Test results
[0076] See also Figure 4 , Figure 4 (a) is a three-dimensional schematic diagram of a Si / W / WOx / W / HZO / W capacitor prepared in an embodiment of the present invention; Figure 4 (b) Cross-sectional image of a representative Si / W / WOx / W / HZO / W capacitor obtained by HRTEM. Figure 4 (c) EDS image corresponding to Figure (b).
[0077] HRTEM testing and EDS analysis show that the atomic layer deposition process can accurately control the thickness of the HZO ferroelectric film. It can be observed that the thickness of the HZO ultra-thin ferroelectric film is about 5nm. The HZO film is well crystallized and has a polycrystalline structure. The grains run through the entire film. It is also observed that the dead layer at the interface between the HZO ferroelectric film and the metal electrode is thin and the degree of oxidation is light. The EDS image reveals that the interface between different ferroelectric film layers in the device is clear; the mutual diffusion phenomenon between various elements (Hf, Zr, W and O) is light, which significantly reduces interface defects and lays the foundation for improving ferroelectric durability.
[0078] (II) Crystallization analysis of Si / W / WOx / W / HZO / W capacitors
[0079] 1. Test equipment
[0080] X-ray diffractometer (X'Pert PRO PANalytical)
[0081] Test conditions: The preset incident angle is 0.5-2.5°, and the 2θ scanning range is 25-33°.
[0082] 2. Test results
[0083] See also Figure 5 , Figure 5 (a) is the GIXRD diffraction spectra of the HZO ultra-thin ferroelectric film in the range of 25° to 33° of the Si / W / WOx / W / HZO / W capacitor in the embodiment of the present invention and the Si / W / HZO / W capacitor in the comparative example; Figure 5 (b) and Figure 5 (c) is the Gaussian peak fitting diagram of the GIXRD diffraction peak; Figure 5 (d) is the relative proportion of o-phase and t / m-phase in the HZO ultra-thin ferroelectric film in the embodiments of the present invention and the comparative examples.
[0084] like Figure 5As shown in (a), the grazing incidence X-ray diffraction test shows that the HZO ultra-thin ferroelectric films with different structures all have excellent crystallinity, and the main diffraction peak of the embodiment slightly drifts to the left. Figure 5 As shown in (b) and (c), the o-phase (30.5°) and t-phase (30.8°) of the main diffraction peaks coexist. The relative proportion of the o / t phase in the ferroelectric film is estimated by semi-quantitative Gaussian fitting of the GIXRD diffraction peaks. Figure 5 (d) The corresponding fitting calculation results are summarized. It can be observed that the ferroelectric o-phase ratio of the embodiment Si / W / WOx / W / HZO / W capacitor is higher than that of the comparison example Si / W / HZO / W capacitor, indicating that the structure is more conducive to the stability of the ferroelectric o-phase and has better ferroelectric properties.
[0085] (III) PV test
[0086] 1. Test equipment
[0087] Ferroelectric Tester (Radiant Precision Workstation)
[0088] Test conditions: The polarization-electric field (PV) hysteresis loop of the ferroelectric capacitor is measured using a 10kHz bipolar triangle wave, without applying a wake-up procedure
[0089] 2. Test results
[0090] See also Figure 6 , Figure 6 (a) and Figure 6 (b) is the PV loop of the HZO ultra-thin ferroelectric film of the comparative example and the embodiment; 6(c) is the 2Pr of the HZO film of the comparative example and the embodiment; Figure 6 (d) is the 2Vc of the HZO ultra-thin ferroelectric film of the comparative example and the embodiment; Figure 6 (e) is the PV loop of the HZO ultra-thin ferroelectric film of the comparative example and the embodiment at a scanning voltage of ±2.5V; Figure 6 (f) is the PV loop of the PUND test of the HZO ultra-thin ferroelectric film of the comparative example and the embodiment at a scanning voltage of ±2.5V.
[0091] from Figure 6(a) and 6(b) show that the Si / W / WOx / W / HZO / W capacitor of the embodiment can obtain good PV hysteresis loops at different scan voltages compared to the Si / W / HZO / W capacitor of the comparative example, and reaches a high 2Pr value of 42.6μC / cm2 at a lower scan voltage of ±1.5V, while the PV hysteresis loop of the comparative example is slightly circular due to the higher leakage current. As shown in Figures (c) and 6(d), the 2Pr value and 2Vc value of the HZO film increase with the increase of the scan voltage, wherein the 2Pr value of the embodiment is higher than that of the comparative example at different scan voltages, while the 2Vc value of the embodiment is lower than that of the comparative example, achieving the reduction of the coercive field without reducing the ferroelectric polarization value, which is beneficial for the ferroelectric memory device to obtain a large storage window and improve the durability of the device. As shown in Figures (e) and 6(f), in the PV hysteresis loop under the same ±2.5V scanning voltage, the embodiment and the comparative example have 2Pr values of 57.4μC / cm2 and 49.5μC / cm2 respectively. The PUND test can eliminate the influence of leakage current on the ferroelectric polarization value. In the PUND test PV hysteresis loop under the same ±2.5V scanning voltage, the embodiment and the comparative example have 2Pr values of 54.3μC / cm2 and 38.2μC / cm2 respectively, which further confirms that the HZO ultra-thin ferroelectric film of the Si / W / WOx / W / HZO / W capacitor structure prepared by the present invention has better ferroelectricity. Figure 6 (g) Figure 6 (h) Figure 6 (i) and (c) show a comparison of the PV loops of the HZO ultra-thin ferroelectric film of the comparative example and the example tested by randomly selecting 50 independent devices under a scanning voltage of ±2 V. The PV hysteresis loops of the comparative example are mostly slightly circular, and 14 of the 50 randomly selected independent devices fail due to the large leakage current, while the PV hysteresis loops of the comparative example are good and only 2 devices fail. Therefore, the device yield of the comparative example is only 76%, while that of the example is 96%, which indicates that the uniformity of the HZO ultra-thin ferroelectric film of the Si / W / WOx / W / HZO / W capacitor structure prepared by the present invention is significantly improved.
[0092] (IV) Fatigue test
[0093] See also Figure 7 , Figure 7 (a) The pulse is ±1.25V / 10 5 Fatigue characteristics comparison chart at Hz; Figure 7 (b) shows the HZO ultra-thin ferroelectric film of the embodiment at different switching voltages of ±1.25 to 2 V / 10 5 Comparison of fatigue characteristics at Hz.
[0094] It can be seen from the figure that under short pulse (±1.25V 100k Hz), the HZO ultra-thin ferroelectric film of the embodiment Si / W / WOx / W / HZO / W capacitor and the comparative example Si / W / HZO / W capacitor can be observed to have a high current density of up to 10 9 However, the HZO ultra-thin ferroelectric film in the comparative example only lasted for 10 5 After 10 cycles, obvious polarization decay was observed. In the HZO ultra-thin ferroelectric film of the embodiment, better fatigue properties were observed. 9 After the first cycle, no obvious polarization decay was observed. HZO ferroelectric films will produce certain defects during the polarization reversal process. A lower coercive field means a lower polarization reversal voltage, which avoids defects under high reversal voltage and enhances fatigue properties.
[0095] (V) Leakage current-voltage characteristics
[0096] 1. Test equipment
[0097] Semiconductor device analyzer (Agilent B1500A)
[0098] 2. Test results
[0099] See also Figure 8 , Figure 8 1 is a comparison diagram of the leakage current-voltage (IV) characteristics of the HZO ultra-thin ferroelectric film of the Si / W / WOx / W / HZO / W capacitor of the embodiment and the Si / W / HZO / W capacitor of the comparative example.
[0100] As can be seen from the figure, the HZO ultra-thin ferroelectric film of the embodiment is observed to have lower leakage current and higher breakdown voltage, which is due to the thinner interface dead layer and fewer oxygen vacancies in the capacitor structure of the embodiment. The lower leakage current is beneficial to improving the durability of the film.
[0101] (VI) PFM ferroelectric domain polarization reversal test
[0102] 1. Test equipment
[0103] Atomic force microscope (cypher)
[0104] 2. Test results
[0105] See also Fig. 9 , Fig. 9 (a) and Fig. 9 (b) is a PFM test comparison diagram of the HZO ultra-thin ferroelectric film of the comparative example and the embodiment at ±5V writing and ±0.5V reading; Fig. 9 (c) and (d) are the phase loops of the HZO ultra-thin ferroelectric film of the comparative example and the embodiment at ±5V PFM single point test; Fig. 9 (e) and (f) are the phase loop and amplitude response loop of the HZO ultra-thin ferroelectric film of the comparative example and the embodiment under the PFM single point test of ±5V.
[0106] from Fig. 9 It can be seen from (a) and 6(b) that after the HZO ultra-thin ferroelectric film of the embodiment Si / W / WOx / W / HZO / W capacitor and the comparative example Si / W / HZO / W capacitor is written at ±5V and read at 0.5V, the HZO ferroelectric film is spontaneously polarized upward, and the downward voltage will cause it to flip. Among them, the phase flip contrast of the embodiment is larger, indicating that the HZO ultra-thin ferroelectric film of the capacitor structure of the present invention has more excellent ferroelectric properties. Fig. 9 The phase and amplitude loops of the single points in (c)-(f) show that the ferroelectric polarization reversal angle of the HZO ultra-thin ferroelectric film of the embodiment and the comparative example can reach the standard 180° at a voltage of ±5V, and the amplitude response is relatively large.
[0107] In summary, the six-layer ultra-thin hafnium oxide ferroelectric film capacitor prepared by the present invention has the following characteristics:
[0108] (1) High ferroelectric polarization value at low driving voltage;
[0109] (2) Excellent fatigue properties, i.e. durability;
[0110] (3) Has lower leakage current.
[0111] Compared with the prior art, the present invention innovatively constructs a six-layer ferroelectric capacitor structure of substrate / bottom electrode layer / oxide intercalation layer / metal layer / HYO ferroelectric ferroelectric film layer / top electrode, which can effectively suppress the production of interface dead layer and excessive oxygen vacancies at the bottom of HYO ferroelectric film, and promote the formation of ferroelectric orthorhombic phase in ferroelectric film by rapid annealing, which not only improves its ferroelectricity but also reduces its coercive field and leakage current, and enhances its fatigue characteristics; at the same time, the preparation process is simple and controllable. The present invention adopts the method of atomic layer deposition to prepare the ferroelectric layer of ultra-thin hafnium oxide ferroelectric film capacitor, the ferroelectric film has good quality and ferroelectric performance, and can grow large-area high-quality ferroelectric film with good uniformity, which has the potential for commercial production and application.
[0112] Furthermore, zirconium (Zr) is used to dope hafnium oxide (HfO2) to prepare Hf with high remnant polarization and wide process window. 0.5 Zr 0.5O2 (HZO) ultra-thin ferroelectric film, and before growing the HZO film, an oxide layer and a metal layer are first grown on the bottom electrode layer to construct an interface engineering to inhibit the formation of a dead layer at the interface between the bottom electrode layer and the HZO ferroelectric film and the generation of oxygen vacancies, thereby regulating the proportion of ferroelectric o-phase and t-phase structures formed in the rapid annealing process of the grown HZO film, thereby reducing the coercive field and leakage current of the HZO ferroelectric film, so that the HZO ultra-thin ferroelectric film capacitor has excellent fatigue characteristics, and at the same time ensures that the HZO ferroelectric film capacitor has excellent ferroelectricity. The preparation method of the present invention is simple to operate, has strong controllability, and the prepared hafnium oxide-based ferroelectric film is of high quality and good ferroelectric performance.
[0113] application
[0114] The ultra-thin hafnium oxide ferroelectric film capacitor with low driving voltage and high fatigue characteristics prepared by the present invention can be applied to ferroelectric memory and ultra-low power consumption logic devices such as negative capacitance transistors.
[0115] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the embodiments of the present application. The singular forms of "a", "said" and "the" used in the embodiments of the present application and the claims are also intended to include plural forms, unless the context clearly indicates other meanings. It should also be understood that, unless otherwise specified, "multiple" and "several" refer to two or more; "and / or" refers to and includes any or all possible combinations of one or more associated listed items; "first", "second", "third", etc. are only used to distinguish, rather than to describe a specific order or sequence, and cannot be understood as indicating or implying relative importance. When the above description relates to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. In the description of the present application, for those of ordinary skill in the art, the specific meanings of the above terms in the present application can be understood according to the specific circumstances.
[0116] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.
Claims
1. A method for preparing an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization, characterized in that: The following steps are involved: S1 deposits a bottom electrode layer on the substrate; S2 grows an oxide intercalation layer on the bottom electrode layer; S3 growing a metal layer on the oxide intercalation layer; S4 uses a hafnium precursor, a doping element Y precursor, and an oxygen source material to grow a Hf on the metal layer. x Y 1-x O2 ferroelectric thin film layer; S5 in Hf x Y 1-x A top electrode layer is grown on the O2 ferroelectric thin film layer to obtain substrate / bottom electrode layer / oxide intercalation layer / metal layer / Hf x Y 1-x Six-layer structure product of O2 ferroelectric thin film layer / top electrode layer; S6: performing a rapid annealing treatment on the six-layer structure product in an inert atmosphere to obtain an ultra-thin hafnium oxide ferroelectric film capacitor.
2. The method for preparing an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization according to claim 1, characterized in that: The step S2 adopts the atomic layer deposition method, introduces O3 as an oxygen source substance, and grows an oxide intercalation layer with a thickness of 1nm to 5nm on the bottom electrode layer.
3. The method for preparing an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization according to claim 2, characterized in that: The material of the oxide intercalation layer is any one of tungsten oxide, molybdenum oxide, hafnium oxide, zirconium oxide and aluminum oxide.
4. The method for preparing an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization according to any one of claims 1 to 3, characterized in that: In step S3, a metal layer with a thickness of 1 nm to 5 nm is grown on the oxide intercalation layer by magnetron sputtering. The magnetron sputtering conditions are as follows: sputtering power of 20 W to 30 W, sputtering time of 5 s to 60 s, substrate speed of 3 rpm to 10 rpm, heating temperature of 0° C. to 300° C., argon partial pressure of 1.0×10 -1 Pa~5.0×10 -1 Pa.
5. The method for preparing an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization according to claim 4, characterized in that: The material of the metal layer is any one of tungsten (W), gold (Au), nickel (Ni), platinum (Pt), titanium nitride (TiN), molybdenum (Mo), copper (Cu), and ruthenium (Ru).
6. The method for preparing an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization according to claim 1, 2, 3 or 5, characterized in that: The step S4 adopts the atomic layer deposition method to take the doping element Y precursor and the hafnium precursor, introduce O3 as an oxygen source substance, and grow Hf with a thickness of 4nm to 10nm on the metal layer. x Y 1-x O2 ferroelectric thin film layer.
7. The method for preparing an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization according to claim 6, characterized in that: The doping element Y precursor may be a zirconium precursor, a lanthanum precursor, an aluminum precursor, or a silicon precursor.
8. The method for preparing an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization according to claim 7, characterized in that: The Hf x Y 1-x In the O2 ferroelectric thin film layer, x∈(0.2,0.8).
9. The method for preparing an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization according to claim 1, 2, 3, 5 or 7, characterized in that: The step S5 adopts magnetron sputtering method to deposit Hf x Y 1-x A plurality of evenly distributed dot top electrodes are grown on the O2 ferroelectric thin film layer, wherein the diameter of the dot top electrodes is 20um-200um, and the thickness of the dot top electrodes is 30nm-100nm.
10. An ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization, characterized in that: The method for preparing an ultra-thin hafnium oxide ferroelectric film capacitor based on electrode optimization according to any one of claims 1 to 9.
Citation Information
Cited By
A transparent ferroelectric transistor and a method of fabricating the same
CN122662242A